2020
DOI: 10.1002/essoar.10503122.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gravity Wave Breaking and Vortex Ring Formation Observed by PMC Turbo

Abstract:  Gravity wave breaking and associated vortex rings are observed in imaging and lidar data of polar mesospheric clouds  Analysis of the data gives parameters of the gravity wave and rates of energy and momentum transfer due to its breaking  Observed vortex ring parameters agree with predictions by numerical resolutions of gravity wave breaking

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…These and more recent modeling efforts also addressing large-scale KHI and multi-scale dynamics revealed a diversity of instabilities that have enabled interpretations of multiple instability events seen in PMC displays from the ground and stratospheric balloons (Fritts et al, 2014(Fritts et al, , 2019Miller et al, 2015). In several applications, comparisons of observed and modeled instability dynamics have allowed quantitative estimates of implied energy dissipation rates (Fritts et al, 2017;Geach et al, 2020). Most recently, Fritts, Kaifler et al (2020) described two successive mesospheric bores observed in the PMC layer and suggested that they are initiated by high-frequency GWs.…”
Section: 1029/2021jd034643 2 Of 28mentioning
confidence: 99%
See 3 more Smart Citations
“…These and more recent modeling efforts also addressing large-scale KHI and multi-scale dynamics revealed a diversity of instabilities that have enabled interpretations of multiple instability events seen in PMC displays from the ground and stratospheric balloons (Fritts et al, 2014(Fritts et al, , 2019Miller et al, 2015). In several applications, comparisons of observed and modeled instability dynamics have allowed quantitative estimates of implied energy dissipation rates (Fritts et al, 2017;Geach et al, 2020). Most recently, Fritts, Kaifler et al (2020) described two successive mesospheric bores observed in the PMC layer and suggested that they are initiated by high-frequency GWs.…”
Section: 1029/2021jd034643 2 Of 28mentioning
confidence: 99%
“…Early and more recent examples include evidence for various instability dynamics accompanying large-amplitude GWs and strong wind shears being common and widespread. Specific examples seen in NLCs from the ground and PMCs imaged from the stratosphere include large-scale Kelvin-Helmholtz instabilities (KHI; see Baumgarten & Fritts, 2014;Witt, 1962), instability dynamics indicative of GW breaking (Fritts et al, 1993(Fritts et al, , 2017(Fritts et al, , 2019Geach et al, 2020;Miller et al, 2015), and related dynamics accompanying mesospheric bores (Fritts, Kaifler et al, 2020).…”
Section: 1029/2021jd034643 2 Of 28mentioning
confidence: 99%
See 2 more Smart Citations
“…At the average speed of 12.1 m/s of the laser beam at the height of the PMC layer, one 10-s-lidar profile averages over a horizontal distance of 121 m. The spot size of the laser beam at the PMC layer follows from the mean divergence of the laser beam and the slant range. Using a mean divergence angle of 67 µrad , the calculated spot size is 6.3 m. The position of the lidar beam is fixed relative to the FOVs of PMC Turbo's camera systems, 100 which have a pixel size at the position of the lidar beam of 3 m and 8 m, respectively (Kjellstrand et al, 2020) 2018 (Geach et al, 2020). Applying tracking algorithms to small-scale features in series of images acquired by the on-board cameras, the local wind speed can also be derived from measurements (Geach et al, 2020).…”
Section: Introductionmentioning
confidence: 99%